Prediction of price decrease in used cars using decision tree in Habib Car Showroom - Ardiansyah, Muhammad; Tanjung, Mahardika Abdi Prawira (Institute of Computer Science (IOCS), 2024)
This study aims to predict the decline in the price of used cars using the Decision Tree method at the Habib Car Showroom. The main problem at the Habib Car Showroom is that there is no system that can predict the price of cars at the Habib Car Showroom. With this research, the prediction of car prices at the Habib Mobil Showroom will be more objective and very helpful for the Habib Car Showroom. This study predicts through criteria and any damage to the cars at the Habib Car Showroom, such as year of manufacture, engine condition, and body condition. Furthermore, this Decision Tree method is useful for calculating how much the price will drop through the damage to the car that will be seen in the condition of the damage. This study will produce objective and accurate results according to the damage to the car or not damaged to the car, and this study can help the Habib Car Showroom predict prices easily, objectively, and accurately.